Analysis of the Subsection 3.2.7 of the Annex to Regulation (EU) No. 488-2014 concerning the maximum cadmium content in chocolate and derived products under the WTO Sanitary and Phytosanitary rules - Torres Rodríguez, Pamela (2021)
The requirement for maximum levels of cadmium in cocoa and derived products established in subsection 3.2.7 of the Annex to the European Union (EU) Regulation No. 488/2014 shall be in accordance with the World Trade Organization (WTO) Sanitary and Phytosanitary (SPS) rules. Thus, through the dogmatic method it is analysed whether it is a SPS measure that affects international trade and if it complies with the basic principles of the SPS Agreement as if the measure: was issued under the sovereign right of the European Union (EU) Member States (MS) to adopt SPS measures, was adopted to protect human life or health, had scientific basis, and does not imply arbitrary or unjustified discrimination.